The psychiatric interview in clinical practice - MacKinnon, Roger A; Michels, Robert (W.B. Saunders, 1971)
In this extensively revised and expanded new edition of the classic, The Psychiatric Interview in Clinical Practice, the authors continue to address the challenges inherent in clinical interviewing—the complexities of defense mechanisms, conflicts, wishes, and fantasies—as they did in their original 1971 edition while also acknowledging the task of adapting their interview strategies to a new era of psychiatry. New perspectives on psychopathology often emphasize descriptive phenomenological approaches and encourage psychiatric interviewing that is overly focused on describing symptoms and establishing diagnoses. The Psychiatric Interview in Clinical Practice stresses that the clinician needs to learn about patients, their problems, their illness, and their lives. From this readers will understand the universal presence of personality types and the importance of the personality as a determining factor in the unfolding of the psychiatric interview. Students learning psychiatry often ask, \"But what do I say to the patient?\" In 20 new and updated chapters, The Psychiatric Interview answers that question by using clinical vignettes from the authors\' everyday work, what they said in a wide variety of clinical situations and what they felt and thought that led them to say it. Specifically this new edition includes, New chapter sections addressing the process of eliciting a patient\'s psychodynamic history and the role of information technology in the psychiatric interview. New chapters on narcissistic, masochistic, anxious, traumatized, and borderline patients, emphasizing the importance of personality type in determining the evolution of psychiatric disorders and providing copious clinical detail illustrating both what to do and what not to do when interviewing these patients. A new chapter presenting a contemporary perspective on \"the patient of different background,\" in which the authors offer valuable guidance on how to approach racial, ethnic, cultural, age, and sexual-orientation differences between interviewer and patient. Updated chapters on psychotic patients, patients with schizophrenia, and cognitively impaired patients, and on depressed, obsessive-compulsive, and histrionic patients, incorporating new, emotionally moving vignettes of interviewer-patient interchanges garnered from the authors\' extensive clinical experience. Updated chapters on hospitalized, psychosomatic, and emergency patients, which are not only psychotherapeutically instructive but also brimming with practical advice for medical students, house staff, doctors, nurses, and social workers. Although The Psychiatric Interview in Clinical Practice is about psychiatric interviewing, many readers will likely recognize aspects of themselves in some of the clinical descriptions. The hope is that this self-recognition will lead to greater self-understanding and self-acceptance as well as to greater understanding and acceptance of others. The clinical examples are about real people, including the authors themselves, their friends, students, and patients. The authors selected situations or traits that are so common and typical that nearly all readers would be able to relate to them. The Psychiatric Interview in Clinical Practice promises to be an enjoyable read as well as a tremendous learning experience for trainees in all of the mental health professions, from medical students and psychiatric residents to psychologists, social workers, and nurses.
Keywords: psychoterapie; Psychopathology; klinické lékařství; Clinical Medicine; psychologie, klinická psychologie; psychiatrie; Psychotherapy; rozhovory jako téma; Interviews as Topic; interview psychologický; psychopatologie; Interview, Psychological